2011
DOI: 10.1007/s11095-011-0541-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Mono-, Di- and Triglyceride of Medium Chain Fatty Acids by Lipid/Surfactant/Water Phase Diagram, Solubility Determination and Dispersion Testing for Application in Pharmaceutical Dosage Form Development

Abstract: PurposeTo compare physiochemical properties of mono-, di- and triglycerides of medium chain fatty acids for development of oral pharmaceutical dosage forms of poorly water-soluble drugs using phase diagrams, drug solubility, and drug dispersion experiments.MethodsPhase diagrams were prepared using a monoglyceride (glycerol monocaprylocaprate: Capmul MCM® EP), a diglyceride (glycerol dicaprylate) and two triglycerides (glycerol tricaprylate: Captex 8000®; caprylic/capric triglycerides: Captex 355 EP/NF®) in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 44 publications
6
74
0
1
Order By: Relevance
“…It was recently noted that the simple weighted average equation worked well in estimating solubility of danazol in two and three component lipid mixtures using Cremophor EL and mono, di and triglyceride mixtures of caprylic/capric acid (15). Our research has demonstrated that this simple relation is broad in its application for acidic, basic and neutral drug molecules covering a wide range in physicochemical properties, and for the major lipids that are used in formulations.…”
Section: Discussionmentioning
confidence: 57%
“…It was recently noted that the simple weighted average equation worked well in estimating solubility of danazol in two and three component lipid mixtures using Cremophor EL and mono, di and triglyceride mixtures of caprylic/capric acid (15). Our research has demonstrated that this simple relation is broad in its application for acidic, basic and neutral drug molecules covering a wide range in physicochemical properties, and for the major lipids that are used in formulations.…”
Section: Discussionmentioning
confidence: 57%
“…In such complex dispersions, there is only a moderate intestinal permeation enhancement action of acyl glycerols compared to those of soluble surfactants (C 8 , or glyceride ethoxylates). The intestinal epithelial surface area exposed to acyl glycerols is increased by formulation in emulsified forms with soluble surfactants such as Cremophor®, demonstrating the positive interaction between the two types of surfactants [269].…”
Section: Case 8: Acyl Glycerolsmentioning
confidence: 99%
“…Such formulation minimizes chemical alterations on biological pathways but promotes physical-structural disruption of cell membrane, a mechanism previously reported to reduce the induction of bacterial drug resistance (13). For in vivo applications, this working mechanism is further ensured by a liposome formulation, in which the lipid bilayers protect LLA molecules from the damaging environment of the stomach and prevent potential oxidation and enzymatic degradation (12,13).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the amphiphilic properties of FFAs allow for direct incorporation into the lipid bilayer membrane of phospholipid liposomes with a high loading yield (12). The vast success of liposomes as an approved delivery vehicle bestows excellent opportunities on FFAs for translational testing and clinical use.…”
mentioning
confidence: 99%